Kostnads- och miljöeffektiva uppvärmningssystem - En fallstudie av flerbostadshuset Vadden i Skövde - Haglund,Johan; Hansson,Marcus (2009)
The purpose of this report is to compare different heating devices for future apartment blocks. The compared heating devices were district heating, geothermal heating, pellets heating and pellets heating combined with solar heating. The two main elements in the report compare the different alternatives with regards to their environmental impact and their lifecycle cost. The heating devices are also being compared as they collaborate with other energy efficiency measures as for example regaining heat from the air in the ventilation system. This report is carried out in cooperation with Peab AB and demarcates to the area around Skövde, Sweden. The apartment block that is being examined is a typical apartment block with an energy usage a little less than the BBR requirement of 110 kWh/m2, year. This report is a case study and therefore no general conclusions can be made. The purpose has been to optimize the apartment block with a focus on environmental impact and the lifecycle cost, when using different heating devices. The economical analysis is being done with present value method and takes the lifecycle costs that appear under the investments life span into consideration. The costs are divided into investment-, installation-, maintenance-, repair- and running costs. To a big extent the costs are from the area around Skövde, for example, local entrepreneurs. What kind of environmental affect each heating device causes is demarcated to the emissions of carbon dioxide. Primary energy factors for carbon dioxide come from the Swedish Energy Agency and they are being compared with a margin energy perspective as well as an average energy perspective. Results in this report show a big dispersion in the lifecycle costs and environmental affects that are caused by each heating device. According to the enquiry the best heating device all together is district heating. Heating with pellets is currently the best option from an environmental point of view, but also the most expensive alternative from a lifecycle cost perspective. In addition, the results show that just a small usage of electricity causes a great emission of carbon dioxide. This means that heating pumps are bad alternatives from an environmental point of view. However, it’s not bad to reduce the energy usage with a small amount of electricity, like for example using FTX-ventilation. The conclusion is that costs and environmental effects are substantially reduced when the energy usage is lowered.
Keywords: energieffektivisering; uppvärmningssystem; energianvändning; lcc; koldioxidutsläpp